How male and female bosses learn to manage: Gender differences are important, but can also be misleading. Issue 10 (14th September 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Explores differences in the entrepreneurial experiences of men and women, including what and how entrepreneurs of both sexes learn. Differences in behavioral patterns include a greater tendency for men to learn from other professional stakeholders while women turned typically to a narrower group of people, more often friends and family. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.